2009
DOI: 10.1677/erc-08-0081
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of papillary thyroid carcinomas without BRAF mutation or RET/PTC rearrangement: relationship with clinico-pathological features

Abstract: About 60-70% of papillary thyroid carcinomas (PTC) present a BRAF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…Although this result was not the main focus of our study, it is noteworthy in the context of the molecular PTC background and recent studies. A similar distribution of asymptomatic thyroids and PTCs harboring BRAF , RET , and RAS alterations was observed also by Durand et al [ 45 ], who performed hierarchical clustering exclusively on the published Giordano PTC samples using 51 genes differentially expressed between their BRAF / RET (+) PTCs and PTC(−). We confirmed that the observed clustering of PTCs with distinct molecular events was not an artifact of the Giordano et al data, but rather an inherent feature of PTC.…”
Section: Discussionsupporting
confidence: 74%
“…Although this result was not the main focus of our study, it is noteworthy in the context of the molecular PTC background and recent studies. A similar distribution of asymptomatic thyroids and PTCs harboring BRAF , RET , and RAS alterations was observed also by Durand et al [ 45 ], who performed hierarchical clustering exclusively on the published Giordano PTC samples using 51 genes differentially expressed between their BRAF / RET (+) PTCs and PTC(−). We confirmed that the observed clustering of PTCs with distinct molecular events was not an artifact of the Giordano et al data, but rather an inherent feature of PTC.…”
Section: Discussionsupporting
confidence: 74%
“…In rat thyroid PCCL3 cells conditionally expressing oncogenic BRAF, increased invasion into Matrigel was observed compared with cells expressing RET/PTC3 in vitro, which was consistent with the biological behavior of human PTC (5). In addition, PTC without the BRAF V600E mutation mainly corresponded to FV-PTC, and maintained a thyroid differentiation expression level close to that of normal tissue and thus had a better prognosis than PTC with the gene alteration (6). Furthermore, the BRAF V600E mutation may induce genetic instability in PTC, facilitating secondary genetic alternation of members of the PI3k/Akt pathway that may induce PTC progression to a more aggressive thyroid cancer (7).…”
Section: Introductionsupporting
confidence: 72%
“…Numerous studies have demonstrated an association between the BRAF V600E mutation with aggressive clinicopathological characteristics of PTC, including extrathyroidal invasion, LNM, advanced tumor-node-metastasis stage, loss of radioiodine avidity and disease recurrence (5)(6)(7). BRAF mutation presents a low positive predictive value (28%) and a high negative predictive value (87%) for PTC recurrence, suggesting that BRAF mutational status in clinical management of PTC should be used with caution.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that mutational status was more highly correlated to gene expression than morphology, confirming the previous observation (Fagin 2004) of BRAF and RET/PTC mutations as dominant alternative molecular events in PTC. The distinct differences in gene profile between PTC without BRAF mutations or RET/PTC rearrangements when compared to PTC with this mutations, were confirmed by others (Durand et al 2009). However, similarities were also obvious: it was shown that BRAF mutations and RET/PTC rearrangements resulted in similar gene expression profile and led to decreased expression of genes related to thyroid differentiation (e.g.…”
Section: Papillary Thyroid Cancersupporting
confidence: 59%